Reply to Comment by D. Jiang on “Pressure‐to‐Depth Conversion Models for Metamorphic Rocks: Derivation and Applications” - A. Bauville; P. Yamato (Geochemistry, Geophysics, Geosystems, 2021)
Abstract In our study (Bauville & Yamato, 2021, https://doi.org/10.1029/2020gc009280), we derived simple formulas for pressure‐to‐depth conversion that allow (or not) to take into account deviatoric stresses. We then tested them against a data set of pressure from high‐pressure (HP) metamorphic rocks. In his comment, Jiang argues that the classical pressure‐to‐depth conversion, which assumes negligible deviatoric stresses (i.e., lithostatic pressure assumption) (a) provides a better explanation of the data and (b) is the only acceptable pressure‐to‐depth conversion method from the point of view of rock mechanics. We disagree with both arguments because (a) although Jiang's explanation is plausible, it does not falsify alternative models. As we concluded in Bauville and Yamato, several models explain equally well the data, and pressure data alone is not enough to validate or falsify any of these models. (b) There is a growing corpus of evidence that even HP metamorphic rocks undergo large deviatoric stress and can record even transient events in their mineralogical assemblage. Finally, Jiang criticizes that we used terms related to deformation loosely to illustrate stress concepts, and that our proposed method of falsification based on markers of deformation may be infeasible for HP metamorphic rocks. We take here the opportunity to clarify all these aspects.